2017
DOI: 10.1177/1947603517710307
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Allograft Transplantation and Opening Wedge Tibial Osteotomy: Clinical Results of a Combined Single Procedure

Abstract: Objective To evaluate the outcome of patients who have undergone simultaneous osteotomy and osteochondral allograft (OCA) transplantation. Our hypothesis is that use of high tibial osteotomy and fresh OCA in a combined procedure is safe and effective without increasing morbidity in comparison to OCA alone. Design A case series of 17 patients underwent tibial osteotomy and simultaneous OCA during a single surgery. Osteotomy was indicated when axial alignment was within the affected compartment. Patients had a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…However, taken together with previous studies documenting safety and efficacy of concurrent or staged realignment osteotomies in conjunction with OCA transplantation, best current evidence suggests continued clinical use and evaluation toward optimizing osteotomy indications, type, and timing are warranted. 2,14,40,41 While decision-making regarding the type of realignment osteotomy, distal femoral, or proximal tibial is primarily governed by the nature and severity of the malalignment, understanding the relative advantages and disadvantages of each with respect to graft healing and integration, joint function and maintenance of corrected alignment, complications, and morbidity is informative for surgeons and patients. It is plausible that DFO might be best performed concurrent with bipolar OCA transplantation, while proximal femoral osteotomy might be best performed as a staged procedure, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…However, taken together with previous studies documenting safety and efficacy of concurrent or staged realignment osteotomies in conjunction with OCA transplantation, best current evidence suggests continued clinical use and evaluation toward optimizing osteotomy indications, type, and timing are warranted. 2,14,40,41 While decision-making regarding the type of realignment osteotomy, distal femoral, or proximal tibial is primarily governed by the nature and severity of the malalignment, understanding the relative advantages and disadvantages of each with respect to graft healing and integration, joint function and maintenance of corrected alignment, complications, and morbidity is informative for surgeons and patients. It is plausible that DFO might be best performed concurrent with bipolar OCA transplantation, while proximal femoral osteotomy might be best performed as a staged procedure, or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the role of specific previous or concurrent procedures on the final outcome is unknown, and prior published studies reported good outcomes after previous or concurrent osteotomies. 9,14 In conclusion, magnitude of graft-recipient AP mismatch was not associated with OCA failure or patientreported outcome scores at midterm follow-up. While commercial allograft vendors continue to provide the AP and ML dimensions of the hemicondyle grafts for surgeons to perform graft-recipient size matching, these results suggest that any AP length mismatch within the limits measured here is not a contraindication for graft acceptance.…”
Section: Discussionmentioning
confidence: 75%
“…This may be secondary to multiple studies that have demonstrated mixed results with regard to outcomes, complication rates and reoperation rates following osteotomy. [27][28][29][30][31]…”
Section: Discussionmentioning
confidence: 99%